TRANSFORMASI RUANG DAN PERLETAKAN RUANG PADA RUMAH TRADISIONAL DURI - Abidah, Andi (Universitas Negeri Makassar, 2013)
Duri traditional house is one of heritage building in South Sulawesi the position of between buginese and torajanese. It have form the same bugis traditional houses as use longtang system. In the past different buginess and Duri is function of every lontang but this now function lontang was the same buginese house. Beside that transformation space of Duri traditional houses of front space and tamping space. Usually space transformation based of necessary of dweller. Keywords: duri traditional, longtang, transformation space